ChemInform Abstract: Angle‐Resolved Valence Shell Photoelectron Spectroscopy of Neutral Nanosized Molecular Aggregates. Issue 20 (20th May 2014) - Signorell, Ruth; Yoder, Bruce L.; West, Adam H. C.; Ferreiro, Jorge J.; Saak, Clara‐Magdalena
Abstract Review: 67 refs.